Penerapan Budaya Inovasi Dengan Mengadopsi Konsep Kaizen (Continuous Improvement) di PT. Petrosida Gresik - Oldive Meigres Zenit; Sukaris Sukaris (Universitas Muhammadiyah Gresik, 2020)
Background - Innovation culture is a very important thing to be applied to a company with the purpose of maintaining the existence and survival of the company. The level of success in doing this innovation significantly depends on the ability, skills and interpreting the rapidly changing environment. In addition, employee involvement also influences the success of innovation. Innovation itself is often associated with KAIZEN or in Japanese terms it means